Patient Satisfaction With Medications for Opioid Use Disorder Treatment via Telemedicine: Brief Literature Review and Development of a New Assessment - Cole, Thomas O.; Robinson, Darlene; Kelley-Freeman, Andrea; Gandhi, Devang; Greenblatt, Aaron D.; Weintraub, Eric; Belcher, Annabelle M. (Frontiers in Public Health, 2021)
Telemedicine is increasingly being used to treat patients with opioid use disorder (OUD). It has particular value in rural areas of the United States impacted by the opioid crisis as these areas have a shortage of trained addiction medicine providers. Patient satisfaction significantly impacts positive clinical outcomes in OUD treatment and thus is of great clinical interest. Yet little is known regarding patient satisfaction with the increasingly important platform of telemedicine-delivered medications for opioid use disorder (tMOUD). The goal of this review is to provide a summary of the existing literature regarding patient satisfaction with tMOUD. We also submit a novel survey based on an existing framework designed to assess tMOUD satisfaction, and present pilot data (N = 14) acquired from patients engaged in rural tMOUD care. Telemedicine provides a feasible method for delivering MOUD in rural areas, and our survey provides a useful assessment to measure patient satisfaction with tMOUD. In light of the pressing need for innovative and technology-driven solutions to the opioid epidemic (especially in light of the COVID-19 pandemic), future research should focus on the development and refinement of tools to assess the important implementation goal of patient satisfaction.